Carl's doomsday scenario - Dinniman, Matt (Dinniman, Matt. Dungeon crawler Carl, 2024)
"They call it the Over City. A sprawling, once-thriving metropolis devastated by a mysterious calamity. But these streets are far from abandoned. An undead circus trawls the ruins. Murdered prostitutes rain from the sky. An ancient spell is finally ready to reveal its dark purpose. Carl still has no pants. They call it Dungeon Crawler World. For Carl and Donut, it's anything but a game"--